2022
DOI: 10.3390/su14074223
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Development of Industrial Symbiosis in Emerging and Frontier Market Countries: Barriers and Drivers

Abstract: Industrial symbiosis (IS) allows the use of the resources of a productive chain, based on collaboration between companies, finding ways to use the waste of one as inputs or raw materials for the other entity. IS seeks to generate environmental sustainability, maximize resources, and generate social, environmental, and economic benefits based on the physical exchanges of waste, residues, and materials, which generate various advantages for companies and environmental benefits for society. Over the years, resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…Consequently, it is curtailing emissions and yielding economic dividends for the industries. Therefore, the penchants for such initiatives are encouraging among the industrialized nations but far from satisfactory in developing countries [1,21]. Neves et al [61] observed that developing countries such as India, Bangladesh and Egypt are new entrants in the tradition of synergy practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is curtailing emissions and yielding economic dividends for the industries. Therefore, the penchants for such initiatives are encouraging among the industrialized nations but far from satisfactory in developing countries [1,21]. Neves et al [61] observed that developing countries such as India, Bangladesh and Egypt are new entrants in the tradition of synergy practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, due to the involvement of informal sectors, grey markets and SMEs, most of the waste exchanges remain undocumented in the developing world. Such countries may need a bottom-up approach for industrial symbiosis, which can be facilitated through policies and regulations [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Other papers examine specific barriers which may be found in the case of emerging and frontier markets and some of their findings may be applicable in our case. Those barriers include, among others, financial barriers to promoting, lack of awareness of industrial symbiosis projects, deficiency of regulatory frameworks and lack of infrastructure [27,28]. Hence, looking into the data already collected, through a PESTLE questionnaire in the margins of the SWAN project, in the light of the recent findings on generic and specific barriers to industrial symbiosis and the ways of removing them [25] seems a very interesting and promising research area.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, this development has slowed down in Europe due to several, mostly financial, barriers (e.g., new infrastructure and physical space required, economic crisis and strict financial budget implemented for the majority of companies) [25]. Recent research, however, has identified a number of other generic IS barriers (i.e., governmental, technological, organizational) [26] but also country-specific barriers (i.e., low awareness, lack of infrastructure, absence of regulatory framework) [27,28] which may be found mainly in emerging and frontier economies and can be applicable in the case of the Balkan countries. Thus, there is currently the need for national or regional policy frameworks that will facilitate the implementation of IS, resulting in economic benefits for all stakeholders involved and improvement in the environmental performance of the system.…”
Section: Introductionmentioning
confidence: 99%
“…This involves providing training and resources for park staff and local communities, empowering local communities to engage more effectively in decision-making processes and increasing their understanding of conservation issues [5,9]. Addressing underlying social and economic factors that contribute to conflicts requires collaboration with other sectors such as agriculture, forestry, and urban planning [11,12]. The strategies proposed in this opinion manuscript have important implications for the management of State Parks in Brazil and can serve as a model for other protected areas facing similar challenges [13].…”
Section: Main Textmentioning
confidence: 99%